INFORMATION AND COMMUNICATION TECHNOLOGY FOR INCLUSIVE EDUCATION: A LITERATURE REVIEW AND ITS IMPLICATIONS FOR COMMUNITY SERVICE - Axelon S Renyaan; Guntur Arie Wibowo; Erwin Erwin (Adiba Aisha Amira, 2023)
Inclusive education is an approach that seeks to provide access to quality education for all learners, including those with special needs. Information and Communication Technology (ICT) has been recognized as one of the tools that can advance inclusive education by providing a variety of adaptive and interactive learning tools. This research aims to explore how ICT can be integrated in inclusive education and the impact it has on community service. The research method used in this study was a literature review. The findings show that ICT provides innovative ways of adapting learning materials that support various learning needs and facilitate early intervention and individualized education. The use of assistive communication devices, accessible educational software and interactive media contribute to a more inclusive learning experience. In addition, there was an improvement in teachers' positive attitudes and readiness to implement ICT-supported inclusive learning methods. However, the study also identified barriers, including limited infrastructure availability, lack of training for ICT use, and the need for more adaptive content.